Good and efficient? Women's voice in agriculture - Ralitza Dimova; Ira N. Gang (Rutgers University, Department of Economics, 2015)
The potential of engaging female agricultural producers in high value crop activities has been in the increasing focus of much of the recent development literature and policy discourse. Using a rich representative household survey for Malawi, this work draws a profile of successful women farmers and the policies and interventions associated with this profile. Our study finds that female cash crop decision-making has significant impact on both efficiency and welfare. Female cash crop decision-making is encouraged by female ownership of land, credit allocations to women, and village-level infrastructure (development agencies, savings and credit unions).
Keywords: 330